2016
DOI: 10.1117/1.jbo.21.12.126006
|View full text |Cite
|
Sign up to set email alerts
|

Penetration depth of photons in biological tissues from hyperspectral imaging in shortwave infrared in transmission and reflection geometries

Abstract: Measurement of photon penetration in biological tissues is a central theme in optical imaging. A great number of endogenous tissue factors such as absorption, scattering, and anisotropy affect the path of photons in tissue, making it difficult to predict the penetration depth at different wavelengths. Traditional studies evaluating photon penetration at different wavelengths are focused on tissue spectroscopy that does not take into account the heterogeneity within the sample. This is especially critical in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 59 publications
1
99
0
Order By: Relevance
“…Penetration depth relates to how deep light or any electromagnetic radiation can penetrate into a material. It is defined as the depth at which the intensity of the radiation inside the material falls to a fraction 1/e (about 37%) of its original value at (or more properly, just beneath) the surface . The remaining 37% of the light will continue to be absorbed in a manner that is less fully understood.…”
Section: Nanoparticles For In Vivo Bioimaging and Theranosticsmentioning
confidence: 99%
“…Penetration depth relates to how deep light or any electromagnetic radiation can penetrate into a material. It is defined as the depth at which the intensity of the radiation inside the material falls to a fraction 1/e (about 37%) of its original value at (or more properly, just beneath) the surface . The remaining 37% of the light will continue to be absorbed in a manner that is less fully understood.…”
Section: Nanoparticles For In Vivo Bioimaging and Theranosticsmentioning
confidence: 99%
“…Low levels of background tissue autofluorescence in the SWIR increase imaging sensitivity to a target fluorophore, and the unique tissue absorption and scattering properties increase contrast of structures at greater penetration depths compared with fluorescence imaging in the NIR (13,(16)(17)(18)(19)(20)(21). However, the adoption of SWIR fluorescence imaging into clinical settings has been prevented by the limited availability of SWIR detection technology and the perceived need for FDA-approved fluorophores with peak emission in the SWIR spectral region.…”
mentioning
confidence: 99%
“…Their results demonstrated that biological imaging in the SWIR region by wavelengths of 1300 to 1375 nm offers the optimal depth of photon penetration and consequently greater transparency of turbid biological media. In spite of these measurements, they were not able to determine the contrast in longer wavelengths beyond 1650 nm due to the lack of highly sensitive camera . In another study by Sordillo et al, total attenuation length of different tissues in the SWIR windows showed higher lengths of tissue transmittance of SWIR light in the sample, in comparison with NIR I light.…”
Section: Bioimaging In Swir Regionmentioning
confidence: 98%
“…The use of visible region of electromagnetic spectrum in the range of 400‐650 nm is suitable to get image from accessible or superficial tissues such as colon and skin, but not for structures locating in the deeper parts of the body such as nucleus or stem of the brain due to the scattering and absorption by tissue components …”
Section: Bioimaging In Swir Regionmentioning
confidence: 99%
See 1 more Smart Citation